Art and Material Culture in the Byzantine and Islamic Worlds : Studies in Honour of Erica Cruikshank Dodd - Baboula, Evanthia,; Jessop, Lesley, (Mediterranean Art Histories ;, 2021)
"Dedicated to Erica Cruikshank Dodd, Art and Material Culture in the Byzantine and Islamic Worlds offers new perspectives on the Christian and Muslim communities of the east Mediterranean from medieval to contemporary times. The contributors examine how people from diverse religious backgrounds adapted to their changing political landscapes and show that artistic patronage, consumption, and practices are interwoven with constructed narratives. The essays consider material and textual evidence for painted media, architecture, and the creative process in Byzantium, Crusader-era polities, the Ottoman empire, and the modern Middle East, thus demonstrating the importance of the past in understanding the present"--